2021
DOI: 10.1021/acs.jafc.1c05827
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Dissipation of Free and Immobilized Water Facilitating the Intramolecular Dehydration of N-Xylosamine and Conversion Improvement of the Amadori Rearrangement Product of Aspartic Acid–Xylose Reaction

Abstract: Compared to the method of aqueous Maillard reaction at atmospheric pressure tandem vacuum concentration, a coupling dehydration method combining spray drying and vacuum drying was used to increase aspartic acid−xylose conversion to the Amadori rearrangement product (ARP). The water activity and moisture states were found as effective indicators to characterize the degree of dehydration of Maillard reaction intermediates and efficient formation of ARP. During the vacuum drying process, the water activity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…† The nuclear magnetic 13 C spectrum could divide the peaks into 10 groups (corresponding to 10 carbons). The presence of the chemical shifts of 174.3 and 171.7 ppm in the 13 C spectrum could prove the presence of -COOH, which was consistent with the findings of Zhang et al 12 According to Kaufmann et al, 26 there were different conformations of…”
Section: Analysis and Characterization Of Fru-aspsupporting
confidence: 89%
See 2 more Smart Citations
“…† The nuclear magnetic 13 C spectrum could divide the peaks into 10 groups (corresponding to 10 carbons). The presence of the chemical shifts of 174.3 and 171.7 ppm in the 13 C spectrum could prove the presence of -COOH, which was consistent with the findings of Zhang et al 12 According to Kaufmann et al, 26 there were different conformations of…”
Section: Analysis and Characterization Of Fru-aspsupporting
confidence: 89%
“…Food & Function Amadori ketones in the aqueous phase such as ring-forming and ring-opening ketones in dynamic equilibrium. The chemical shift of 53.0 ppm in 13 C NMR indicated the ring closure of Fru-Asp, 12 instead of the chained keto form. As Hansen et al 10 reported, only one major anomer was observed in the spectra of Fru-Asp consistent with the preference of molecules of this sort for the β-pyranose form.…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…3 During the thermal treatment, nucleophilic addition of the amino group on peptides or amino acids to the carbonyl group on sugars readily occurs, followed by dehydration to form a Schiff base. 4 The subsequent Amadori or Heyns rearrangement of the Schiff base lowers the energy of the molecule and results in a relatively stable deoxyaminoketose or deoxyaminoaldose existing either in the acyclic form or as their cyclic hemiacetal isomers. 5 These Amadori or Heyns rearrangement products (ARP or HRP) are nonvolatile precursors of flavor and browning compounds, and they are regarded as important intermediates of Maillard reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Maillard reaction can take place even at room temperature but is favored by high temperature; thus, it significantly influences the quality and acceptance of the foods prepared through thermal treatment . During the thermal treatment, nucleophilic addition of the amino group on peptides or amino acids to the carbonyl group on sugars readily occurs, followed by dehydration to form a Schiff base . The subsequent Amadori or Heyns rearrangement of the Schiff base lowers the energy of the molecule and results in a relatively stable deoxyaminoketose or deoxyaminoaldose existing either in the acyclic form or as their cyclic hemiacetal isomers .…”
Section: Introductionmentioning
confidence: 99%